Metal/porous silicon Schottky diode structures as sensors - Dzhafarov, Tayyar; Lus, Cigdem Oruc; Aydin, Sureyya; Cingi, Emel (MATERIALS RESEARCH SOC, 2006)
In this work we present data on investigation of the current-voltage and capacitance characteristics of Au/PS Schottky type structures in the presence of different hydrogen-containing solutions (sodium borohydride, sodium tetraborate pentahydrate, glucose, ethanol, methanol, boric acid, benzine, KOH). Generation of the open-circuit voltage and short-circuit current density and capacitance up to 0.55 V, 25 mA/cm(2) and 1 mu F respectively on placing of Au/PS structures in these solutions was discovered. This effect is mainly caused by hydrogen component of solutions. The possible mechanism generation of voltage and capacitance in metal/PS sensors hydrogen-containing solutions is suggested. The advantage of metal/PS Schottky type sensors consists in working without applying external electricity.
Keywords: Engineering; Science & Technology - Other Topics; Instruments & Instrumentation; Materials Science